Pengaruh Likuiditas Dan Profitabilitas Terhadap Kinerja Keuangan Pt Aneka Gas Industri Natar Lampung Selatan - Lusi Mirnawati; Lestari Wuryanti; Bambang Purwanto (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2015)
Abstract. This research aims to analyze and determine the effect of the liquidity and profitability ofthe finacial performance of Varios Industrial Gases Natar PT Southern Lampung. Population in thestudy of financial statements the sample that is used as a 6 period financial statements. Analysis modelused in completing this study is to test the classical assumption of date normality test, autocorrelationtest, multicollineariry test and heteroscedasticity tast. Regarding there is influence between liquidityand profitability on thefinancial perfomance of Various Industrial Gases Natar PT Southem Lampungtext partially or simulteancously.